Effects of two cognitive regulation strategies on the processing of food cues in high restrained eaters. An event-related potential study. (1st September 2015) - Svaldi, Jennifer; Tuschen-Caffier, Brunna; Biehl, Stefanie C.; Gschwendtner, Kathrin; Wolz, Ines; Naumann, Eva
Highlights: We tested emotion regulation (ER) and food processing in restrained eaters (RE). ER significantly reduced P300 and LPP compared to a food control condition. P300 and subjective craving were significantly correlated. Abstract: This study tested the effects of cognitive regulation (CR) on the attentional processing of food cues in restrained eaters (RE) by means of event-related potentials (ERPs). In a within-subject-design, RE ( n = 23) were presented pictures of highly palatable food and office items while ERPs were recorded. Prior to the presentation of the food stimuli, participants were either instructed to engage in reappraisal or to attempt to suppress cravings – both cognitive regulation (CR) strategies – or to simply watch the pictures. Prior to the presentation of the neutral stimuli, participants were instructed to simply watch them. Following each picture presentation, momentary craving was assessed. Main results showed that engaging in CR significantly reduced ERP amplitudes compared to the food watch condition. Passively attending to food pictures yielded significantly higher craving scores compared to engaging in CR. In addition, craving was significantly lower in the reappraisal than in the suppression condition. Therefore, reappraisal could potentially increase the ability to inhibit the appetitive motivation to eat.